Juridical Analysis Of The Headman's Authority In Village Fund Management (Case Study Of Law Number 6 Of 2014 Concerning Villages In Lolotwara Village, Lakor District, Southwest Maluku Regency). - Ririhena, KiranaMicha; Ririhena, Micael (Gayaku Publisher, 2023)
Law Number 6 of 2014 explains that the purpose of village development is to improve the welfare of rural communities and the quality of human life as well as poverty reduction through meeting basic needs. Moreover, the development includes building village facilities and infrastructure, developing local economic potential, and sustainable use of natural resources and the environment. This article aims to find out how the authority of the village head in carrying out village fund management, the obstacles they deal with, and how to overcome it in Lolotuara village, Pulau Lakor District, Southwest Maluku Regency. The use of village funds raises a classic problem in the system of using village funds. The allocation does not provide appropriate results for village development. Hence, the allocation of large village funds requires general regulations to clear and accommodating the implementation of its regulations. Eventually, the village head as the highest executive in the village government is able to implement the mandate of the law. Therefore, the objectives of the village law can be realized according to existing regulations.